2019
DOI: 10.3389/fmicb.2019.01808
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Volatile Organic Compounds and Rhizosphere Competence in Mode of Action of the Non-pathogenic Fusarium oxysporum FO12 Toward Verticillium Wilt

Abstract: Verticillium wilts caused by Verticillium spp. are among the most challenging plant diseases to control and affect numerous hosts worldwide. Due to the lack of effective, conventional control methods, integrated control strategies provide a promising approach to manage these diseases. The non-pathogenic Fusarium oxysporum strain FO12 was reported in previous studies to be an effective biocontrol agent against Verticillium dahliae , however, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…However, there are no data available regarding the activity of lipopeptide biosurfactants for B. velezensis OEE1 [ 30 ]. With regard to volatile compounds, they are well known for having antifungal activity, plant growth promoting activity, and inducing systemic resistance [ 73 , 74 , 75 ]. The volatile organic compounds of B. velezensis XT1 inhibited by 34% mycelium growth of V. dahliae , which is comparable to the 40% inhibition reported for B. velezensis OEE1 [ 30 ], although the experimental set up is not exactly the same.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no data available regarding the activity of lipopeptide biosurfactants for B. velezensis OEE1 [ 30 ]. With regard to volatile compounds, they are well known for having antifungal activity, plant growth promoting activity, and inducing systemic resistance [ 73 , 74 , 75 ]. The volatile organic compounds of B. velezensis XT1 inhibited by 34% mycelium growth of V. dahliae , which is comparable to the 40% inhibition reported for B. velezensis OEE1 [ 30 ], although the experimental set up is not exactly the same.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, typical rhizosphere microorganisms are often mobile, and bacteria, protists, and some rapidly growing fungi (e.g., “sugar fungi,” de Boer et al, 2006 ) move in parallel to the exudate pulse along the root ( Hünninghaus et al, 2019 ). These organisms are generally characterized by high “rhizosphere competence,” being both, well adapted to fast colonization and fierce competitors for root colonization sites ( Lugtenberg et al, 2001 ; Kamilova et al, 2005 ; Schreiter et al, 2014 , 2018 ; Mulero-Aparicio et al, 2019 ).…”
Section: Plant Selection For Microbial Traitsmentioning
confidence: 99%
“…Likewise, treatments with conidial suspensions or chlamydospores of FO12 were effective in reducing both the inoculum density of V. dahliae in the soil and the VWO severity [169]. As for the biocontrol mechanism involved, the effect of secondary metabolites produced by FO12 against V. dahliae was investigated [169,170]. In vitro experiments indicated that the metabolites produced by FO12 had little effect on the inhibition of V. dahliae mycelial growth, suggesting that the antagonistic effect relies on the presence of FO12 alive and on a direct interaction with the pathogen [169].…”
Section: The Continuous Search For Effective Biological Control Agentmentioning
confidence: 99%
“…In addition, the production of VOC by FO12 in the presence of V. dahliae has been reported. Several of these compounds have been previously involved in antifungal activity and biological control [170].…”
Section: The Continuous Search For Effective Biological Control Agentmentioning
confidence: 99%